DIGITAL TECHNOLOGIES – A MEANS OF CONDUCTING INDUSTRIAL TRAINING LESSONS IN THE CONDITIONS OF MODERN CHALLENGES (Innovative professional education, 2023)
The article reveals the essence of using digital technologies in the educational process. Forms of distance learning, their advantages and disadvantages in training qualified workers are considered. The possibility of using mobile devices when studying educationalmaterial is noted, which contributes to better assimilation of new material, increasing the level of cognitive interest of students, and the formation of professional and informational culture.
Keywords: digitalization, digital technologies, distance learning, health education, virobniche navchannya, study, meister